Derivation of primitive neural stem cells from human‐induced pluripotent stem cells. Issue 18 (20th June 2019) - Shin, Woo Jung; Seo, Ji‐Hye; Choi, Hyun Woo; Hong, Yean Ju; Lee, Won Ji; Chae, Jung Il; Kim, Sung Joo; Lee, Jeong Woong; Hong, Kwonho; Song, Hyuk; Park, Chankyu; Do, Jeong Tae
Abstract: Human‐induced pluripotent stem cells (hiPSCs) have facilitated studies on organ development and differentiation into specific lineages in in vitro systems. Although numerous studies have focused on cellular differentiation into neural lineage using hPSCs, most studies have initially evaluated embryoid body (EB) formation, eventually yielding terminally differentiated neurons with limited proliferation potential. This study aimed to establish human primitive neural stem cells (pNSCs) from exogene‐free hiPSCs without EB formation. To derive pNSCs, we optimized N2B27 neural differentiation medium through supplementation of two inhibitors, CHIR99021 (GSK‐3 inhibitor) and PD0325901 (MEK inhibitor), and growth factors including basic fibroblast growth factor (bFGF) and human leukemia inhibitory factor (hLIF). Consequently, pNSCs were efficiently derived and cultured over a long term. pNSCs displayed differentiation potential into neurons, astrocytes, and oligodendrocytes. These early NSC types potentially promote the clinical application of hiPSCs to cure human neurological disorders. Abstract : Primitive neural stem cells (pNSCs) can be generated from human‐induced pluripotent stem cells. pNSCs expressed early‐stage NSC markers SOX1, PAX6, and NESTIN and did not form teratomas. pNSCs showed long‐term self‐renewal capacity in in vitro culture system. pNSCs displayed differentiation potential into neurons and glial cells.